EFFECT OF MAGNETICALLY TREATED WATER ON THE QUALITY OF TOMATO - Yusuf, K. O.; Ogunlela, A. O. (Kathmandu University Journal of Science, Engineering and Technology, 2016)
This study was conducted to determine the effect of magnetically treated water on the quality of tomato. The values of magnetic flux densities used for treating the irrigation water were 124, 319 and 719 G produced from electromagnet with direct current. The tomato (variety UC82B) was planted in 28 buckets in a transparent garden shed for 130 days and irrigated with magnetically treated water and non–magnetically treated water. The mean values of vitamin A and vitamin C were higher with the tomato irrigated with magnetically treated water than tomato irrigated with non – magnetically treated water. The lead was slightly higher with tomato irrigated with magnetically treated water than the non–magnetically treated water. The values of vitamin A with water treated by 124 G, 319 G and 719 G were 0.68 mg/kg, 0.74 mg/kg and 0.80 mg/kg, respectively while vitamin A for non-magnetically treated water was 0.73 mg/kg. The values of vitamin C with water treated by 124 G, 319 G and 719 G were 117.30 mg/kg, 114.03 mg/kg and 115.10 mg/kg, respectively while vitamin C for non-magnetically treated water was 113.93 mg/kg. The value of lead was 0.083, 0.090 and 0.083 mg/kg for magnetically treated water while that of non-magnetically treated water was 0.07 but WHO Standards (permissible limits) for lead in tomato is 0.1 mg/kg. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. 2, 2016, page: 29-33